Zhuang Bai Nang Hai Ritual, Emotional Resonance, and Social Adaptation Stress in Retired Women: An Empirical Study - Wan, Lihan (Transactions on Social Science, Education and Humanities Research, 2026)
Women in China have a tendency to retire between the ages of 50 and 55 and then they have about three decades of non-working life, which is about one-third of their entire life. Social adaptation stress arises as an urgent mental health issue during this long duration but there are few culturally grounded interventions. This paper examines how Zhuang Bai Nang Hai ritual participation is related to social adaptation stress among retired women and emotional resonance is studied as a mediating variable. Ritual movement elements were discovered through ethnographic fieldwork and transformed into a dance movement therapy model using Laban Movement Analysis. The intervention efficacy was assessed using a quasi-experimental design. The main thesis is that the alleviation of social adaptation stress by ritual participation is mainly mediated by emotional resonance as the pathway. Theoretically, this work shifts the study of rituals as descriptive documentation to mechanistic explanation. In practice, it provides empirical basis on the establishment of dance movement therapy practices based on indigenous Chinese cultural practices and provides a culturally consistent intervention protocol based on psychological wellbeing of retired women.